Gut adaptation after metabolic surgery and its influences on the brain, liver and cancer. Issue 10 (October 2018) - Sinclair, Piriyah; Brennan, Donal; le Roux, Carel
Abstract Metabolic surgery is the best treatment for long-term weight loss maintenance and comorbidity control. Metabolic operations were originally intended to change anatomy to alter behaviour, but we now understand that the anatomical changes can modulate physiology to change behaviour. They are no longer considered only mechanically restrictive and/or malabsorptive procedures; rather, they are considered metabolic procedures involving complex physiological changes, whereby gut adaptation influences signalling pathways in several other organs, including the liver and the brain, regulating hunger, satiation, satiety, body weight, glucose metabolism and immune functions. The integrative physiology of gut adaptation after these operations consists of a complex mechanistic web of communication between gut hormones, bile acids, gut microbiota, the brain and both enteric and central nervous systems. The understanding of nutrient sensing via enteroendocrine cells, the enteric nervous system, hypothalamic peptides and adipose tissue and of the role of inflammation has advanced our knowledge of this integrative physiology. In this Review, we focus on the adaptation of gut physiology to the anatomical alterations from Roux-en-Y gastric bypass and vertical sleeve gastrectomy and the influence of these procedures on food intake, weight loss, nonalcoholic fatty liver disease (NAFLD) and cancer. We also aim to demonstrate the underlying mechanisms that could explain how metabolic surgery could be used as a therapeutic option in NAFLD and certain obesity-related cancers. Metabolic surgery is the best treatment for long-term weight loss maintenance and comorbidity control. In this Review, the authors discuss how gut physiology adapts to these procedures and the consequent effects on food intake, weight loss, liver disease and cancer. Key points Gut adaptation after metabolic surgery is pivotal in facilitating weight loss and comorbidity improvement. The complex interactions between the gut–brain–endocrine axis, the gut microbiota and bile acid kinetics are postulated to have a role in reducing food intake and improving metabolic control after metabolic surgery. The integrative physiology of changes in eating behaviour, weight loss, gut hormones, bile acids, gut microbiota and adipocyte-derived factors is also postulated to result in comorbidity improvement. Further research on the mechanistic effects of metabolic surgery on nonalcoholic fatty liver disease and cancer are vital before metabolic surgery can be recommended as a treatment for these conditions.